2021
DOI: 10.1051/0004-6361/202039043
|View full text |Cite
|
Sign up to set email alerts
|

Cosmological constraints on the magnification bias on sub-millimetre galaxies after large-scale bias corrections

Abstract: Context. The study of the magnification bias produced on high-redshift sub-millimetre galaxies by foreground galaxies through the analysis of the cross-correlation function was recently demonstrated as an interesting independent alternative to the weak-lensing shear as a cosmological probe. Aims. In the case of the proposed observable, most of the cosmological constraints mainly depend on the largest angular separation measurements. Therefore, we aim to study and correct the main large-scale biases that affect… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

6
0

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 79 publications
(62 reference statements)
1
20
0
Order By: Relevance
“…The outcome of such a test was that there are no noticeable changes in the spread of the posterior distributions when significantly reducing the cross-correlation data errors. In addition, the findings of González-Nuevo et al (2021) about cosmological parameter constraints point in the same direction: increasing the number of sources in an attempt to diminish the statistical errors does not reduce the uncertainties of the results. This is probably related with the use of a single wide redshift bin and the assumption of no time evolution in the astrophysical HOD parameters.…”
Section: Summary Conclusion and Future Prospectsmentioning
confidence: 95%
See 2 more Smart Citations
“…The outcome of such a test was that there are no noticeable changes in the spread of the posterior distributions when significantly reducing the cross-correlation data errors. In addition, the findings of González-Nuevo et al (2021) about cosmological parameter constraints point in the same direction: increasing the number of sources in an attempt to diminish the statistical errors does not reduce the uncertainties of the results. This is probably related with the use of a single wide redshift bin and the assumption of no time evolution in the astrophysical HOD parameters.…”
Section: Summary Conclusion and Future Prospectsmentioning
confidence: 95%
“…In In this work, we use the angular cross-correlation function measured by González-Nuevo et al ( 2021) using the Tiles area for the same spectroscopic sample. We chose this particular set of measurements based on the analysis performed by González-Nuevo et al (2021), which studied the large-scale biases for different samples and tiling schemes. The measurements from the spectroscopic sample are only affected by the so called integral constraint (IC; Roche & Eales 1999), but the correction for the chosen tiling scheme is almost negligible (IC = 5 × 10 −4 ).…”
Section: Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…In this respect, by comparing the CCF normalisation, we can approximately infer the average richness of previous works related to magnification bias. The CCF that is being used for cosmological analyses (González-Nuevo et al 2017;Bonavera et al 2020;González-Nuevo et al 2021;Cueli et al 2021) is measured using foreground samples built from galaxy catalogues. The values around 100 kpc are similar to the bin 1 or bin 2 measurements, which implies a richness of below 25.…”
Section: Discussionmentioning
confidence: 99%
“…These properties make SMGs promising candidates to be successfully used as a background sample for magnification bias studies, as in González-Nuevo et al (2014 where the CCF was measured with high significance, and as directly observed by Dunne et al (2020) with the Atacama Large Millimetre Array (ALMA). Moreover, the SMGs are used to investigate the halo mass, projected mass density profile, and concentration of foreground samples of quasi-stellar objects (QSOs; Bonavera et al 2019), for cosmological studies (Bonavera et al 2020;González-Nuevo et al 2021;Bonavera et al 2021) and to observationally constrain the halo mass function (Cueli et al 2021, Cueli et al, in prep. ).…”
Section: Introductionmentioning
confidence: 99%